Integrating serum metabolomics and network analysis to explore the antidepressant activity of crocin in rats with chronic unexpected mild stress-induced depression - Yan Luo; Ziyan Zhong; Huan Li; Le Wang; Dongwei Guo; Xuanqi Dong; Jian Liu; Mingxia Xie; Mei Wu; Yun Xiang; Xi Zhang; Pan Meng (Taylor & Francis Group, 2023)
AbstractContext Crocin exhibits anti-depressant properties. However, its underlying mechanisms and its relationship with metabolomics remain unclear.Objective This study elucidates the mechanism of action and potential targets of crocin in treating chronic unexpected mild stress (CUMS)-induced depression in rats.Materials and methods Male Sprague-Dawley (SD) rats underwent 4 weeks of CUMS to establish the depression model. The normal control (distilled water), crocin (25 mg/kg), and fluoxetine (5.4 mg/kg) groups were orally administered for 4-weeks. Behavioural tests evaluated the effects of crocin, while liquid chromatography-mass spectrometry metabolomics identified differential metabolites and their associated metabolic pathways. Subsequently, network pharmacology was utilized to predict the targets of crocin.Results Crocin significantly increased body weight (from 319.16 ± 4.84 g to 325.67 ± 2.84 g), sucrose preference (from 0.46 ± 0.09 to 0.70 ± 0.09), vertical activity (from 2.83 ± 1.94 to 8 ± 2.36), horizontal activity (from 1 ± 0.63 to 4.5 ± 3.08) and decreased immobilization time (from 13.16 ± 2.69 to 3.97 ± 3.00). Metabolomics analysis identified 7 metabolites and 5 associated metabolic pathways. From the combined analysis of network pharmacology and metabolomics, three targets (PRMT1, CYP3A4, and GLB1) are the overlapping targets and the two most important metabolic pathways are tryptophan metabolism and glycerolipid metabolism.Discussion and conclusions This study provides insights into the antidepressant therapeutic effect of crocin and its underlying mechanisms. The findings contribute to a better understanding of the metabolic mechanism involved in the anti-depressant effect of crocin, establishing a strong foundation for future research in this area.